2010
DOI: 10.1094/php-2010-0122-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Fungicide and Insecticide Applications on Soybean in Ohio

Abstract: Mid-season applications of Quadris with and without Warrior insecticide were evaluated in 2004 and 2005, and Headline, Folicur, Domark, or Headline plus Folicur were evaluated in 2006, 2007, and 2008 in 37 farm scale studies in Ohio. Producer cooperators selected fields, applied treatments at growth stage R3 and harvested fields. Each trial was rated at growth stage R5 or R6 for incidence and severity of brown spot and frogeye leaf spot. Aphids and foliar disease incidence was low in 2004. Soybean aphids were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 6 publications
4
44
1
Order By: Relevance
“…Similarly, insect pressure was very low and all populations of all observed insect pests were below economic thresholds. While other studies have reported a yield increase for insecticide application in the absence of pest pressure (Dorrance et al, 2010; Henry et al, 2011) the application of an insecticide did not increase soybean yield in this study.…”
Section: Lack Of Treatment Responsescontrasting
confidence: 85%
See 1 more Smart Citation
“…Similarly, insect pressure was very low and all populations of all observed insect pests were below economic thresholds. While other studies have reported a yield increase for insecticide application in the absence of pest pressure (Dorrance et al, 2010; Henry et al, 2011) the application of an insecticide did not increase soybean yield in this study.…”
Section: Lack Of Treatment Responsescontrasting
confidence: 85%
“…However, no above‐threshold insect pests were observed at any of these locations (Henry et al, 2011). A study in Ohio found that the application of a foliar insecticide, lambda cyhalothrin, increased soybean yield in two out of five locations where aphids were not present (Dorrance et al, 2010).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Henry et al (2011) reported a comparable level of yield increase (i.e., 3.5%) when pyraclostrobin was applied to soybean at the R4 growth stage. Other studies reported yield increases ranging from 8 to 19.8% (Bradley and Sweets 2008;Cruz et al 2010;Dorrance et al 2010;Nelson et al 2010;Nelson and Meinhardt 2011); however, as previously discussed, detectable yield increases were inconsistent across siteyears or treatments. In this study, as expected, cultivars that were relatively tolerant to brown spot and demonstrated plant health effects (e.g., cultivar 12, DEKALB 31-10RY) tended to outperform cultivars more susceptible to brown spot with no apparent plant health effects (e.g., cultivar 15, Hyland Seeds HR 12R42) with yields of 4.89 and 4.11 t ha…”
Section: Yieldmentioning
confidence: 79%
“…In essence, strobilurin-treated plants display prolonged ''greening'' (Kyveryga et al 2013), which presumably allows for greater dry matter accumulation through the seed-filling period and higher yields as more photosynthetically efficient leaves are retained longer (Morrison et al 1999;Specht et al 1999;Kumudini et al 2001). However, while strobilurininduced physiological effects demonstrated in soybean (Conrath et al 2004;Nason et al 2007;Fagan et al 2010) increased yield or yield components in some studies (Fagan et al 2010;Henry et al 2011;Masayasu et al 2011), other studies showed that increased yields due to strobilurin fungicides were inconsistent across years and/ or treatment combinations (Bradley and Sweets 2008;Cruz et al 2010;Dorrance et al 2010;Nelson et al 2010;Nelson and Meinhardt 2011;Kyveryga et al 2013) or were nonexistent (Swoboda and Pedersen 2009). Yet, buoyed by high commodity prices (Agriculture and AgriFood Canada 2014), soybean producers are opting to use fungicides to manage foliar diseases (Basu 1980;Melzer and Shan 2013) which rarely cause serious yield losses, compared to soil-borne, seed, or seedling diseases (Wrather et al 2003;OMAFRA 2009).…”
mentioning
confidence: 99%
“…In other studies, strobilurin-induced physiological effects in soybean (Conrath et al 2004;Nason et al 2007;Fagan et al 2010) were shown to increase yield or yield components (Fagan et al 2010;Henry et al 2011;Masayasu et al 2011). However, increased soybean yield due to strobilurin fungicides have been inconsistent across years and/or treatment combinations (Bradley and Sweets 2008;Swoboda and Pedersen 2009;Cruz et al 2010;Dorrance et al 2010;Nelson et al 2010;Nelson and Meinhardt 2011;Kyveryga et al 2013). For dry bean, the physiological effects of strobilurins have been investigated in South America (Rodrigues et al 2009;Demant and Maringoni 2012;Vigo et al 2012).…”
mentioning
confidence: 99%